2016
DOI: 10.21608/ejnf.2016.74897
|View full text |Cite
|
Sign up to set email alerts
|

Productive Peformance, Nutrients Digestibility and Some Serum Metabolic Indices as Affected by Dieatary Supplementation of Copper and Zinc in Egyptian Buffalo Calves

Abstract: his study was designed to evaluate the effects of dietary supplementation of copper (Cu) and zinc (Zn) on productive performance, nutrients digestibility and some serum metabolic indices in Egyptian buffalo calves. A total number of 32 calves averaged 278.8 ± 5.40 kg and 18 months old were divided into four equal groups (8 calves / each). Animals were fed on basal diet containing 4.38 mg Cu and 6.30 mg Zn/kg DM (control) supplemented with 10 mg Cu (T1), 30 mg Zn (T2) and 10 mg Cu plus 30 mg Zn (T3) /kg DM for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…However, Ibrahim (2016) found that maternal Se supplementation improved body gain of their lambs. The beneficial effects of supplemental Se on animal performance was reported to improve birth weight of lambs (Ali et al, 2004) and average body weight for new born lambs (Hefnawy et al, 2014).…”
Section: Body Weight Of Kidsmentioning
confidence: 95%
“…However, Ibrahim (2016) found that maternal Se supplementation improved body gain of their lambs. The beneficial effects of supplemental Se on animal performance was reported to improve birth weight of lambs (Ali et al, 2004) and average body weight for new born lambs (Hefnawy et al, 2014).…”
Section: Body Weight Of Kidsmentioning
confidence: 95%
“…Moreover, Vinu et al (2012) found that supplemented Se-yeast at rate of 0.3 ppm to calves diets did not reveal any significant difference on daily body weight gain as compared with control. However, Ibrahim (2016) found that maternal Se supplementation improved body gain of their lambs. The beneficial effects of supplemental Se on animal performance was reported to improve the birth weight of lambs (Ali et al, 2004) and average body weight for new born lambs (Hefnawy et al, 2014).…”
Section: Body Weight Of Kidsmentioning
confidence: 95%